Locus Of Control Memoderasiwhistleblowing System, Literasi Keuangan, Dan Tindakan Audit Terhadap Kualitas Laporan Keuangan - D. Aditya Dian Aditya; Zaki Baridwan; Endang Mardiati (Jurnal Reviu Akuntansi dan Keuangan, 2023)
Purpose: Knowing the effect of whistleblowing system, financial literacy, and audit actions on the quality of the company's financial statements moderated by the locus of control. Methodology/approach: This type of research is quantitative. Researchers collected data by providing questionnaires to financial employees of tobacco companies in East Java. The Data were analyzed using descriptive analysis test, classical assumption test, hypothesis test, and coefficient of determination test. Findings: This study found that wishtlebowing system, financial literacy, and partial audit actions have a positive and significant effect on the quality of the financial statements of tobacco companies in East Java. As for locus of control can moderate whistleblowing system on the quality of financial statements, locus of control can not moderate financial literacy on the quality of financial statements, and locus of control can weaken the audit action on the quality of financial statements. Practical implications: Later a company management can be helped by the existence of this study in using the strategy and establish rules for the progress of the company related to the quality of financial statements. Originality/value: The novelty of this study on the location of research, moderation variables, and independent variables.